Effect of Nucleus Basalis Magnocellularis Lesions on Memory and Hippocampal Brain-Derived Neurotrophic Factor, IL-1β, Glucose, and Corticosterone Levels in Adult Rats - Hosseini, Nasrin; Radahmadi, Maryam; Alaei , Hojjatallah; Nadjafi, Shabnam (International Clinical Neuroscience Journal, 2021)
Background: The nucleus basalis magnocellularis (NBM) sends projections to the hippocampus that are implicated in learning and memory formation. Despite ample evidence proposing that cognitive function impairment related to neurodegeneration, it may result from alteration of biochemical substances. We aimed to investigate the effects of NBM lesions on the hippocampal interleukin-1beta (IL-1β), brain-derived neurotrophic factor (BDNF), and corticosterone levels, as inflammation markers, and hallmarks of neurodegeneration, stress, and metabolic status. Methods: Thirty-six male Wistar rats were randomly put in control, sham, and NBM-lesioned groups. After inducing the lesion using an intra-NBM injection of 10 μg ibotenic acid (5 μg/μL, each side) in rats, memory was estimated using the passive avoidance test. Moreover, serum and hippocampal IL-1β levels, as well as the hippocampal corticosterone, BDNF, and glucose levels were measured after 42 days. Results: Findings indicated a significant impairment of retention at different intervals in the NBM-lesioned group. BDNF decreased whereas corticosterone, glucose, and IL-1β levels increased in the hippocampus. Also, the levels of serum IL-1β, hippocampal BDNF, corticosterone, and glucose had significant correlations with hippocampal IL-1β levels. Conclusion: The synchronous alterations of some hippocampal factors, including BDNF, corticosterone, IL-1β, and glucose, caused by NBM lesion suggest that their interaction might play a significant role in neurodegeneration and relevant learning and memory impairments.